CLASSIFICATION OF AFFIXES ACCORDING TO THEIR MEANING (Modern education and development, 2025)
This article examines the classification of affixes based on their meaning, focusing on the role these morphemes play in modifying the base words they attach to. It categorizes affixes into various types, including derivational, inflectional, causative, reciprocal, negative, intensive, quantitative, agentive, diminutive, and pejorative. Each category is discussed with relevant examples, showcasing how affixes influence word formation, grammatical structure, and the expression of nuanced meanings. The article highlights the significance of affixes in enriching language and facilitating precise communication. It is a valuable resource for those studying linguistics, morphology, and the dynamics of language evolution.